Unveiling the Factors Behind Delayed Introduction of Complementary Feeding and its Impact on Infant Nutrition: A Case Study in Peshawar, Pakistan : Introduction of Complementary Feeding - Jan, Mir Shakir Ullah; Ullah, Naimat (Pakistan Journal of Health Sciences, 2024)
Timely introduction of complementary feeding (CF) is essential for the health and development of infants. However, delayed initiation of CF can lead to malnutrition and stunted growth. Despite the presence of global guidelines, adherence to recommended feeding practices, particularly in initiating CF late, remains prevalent in developing regions. Objective: To examine the reasons for delayed CF in Peshawar, as well as its impact on infant health. Methods: A Retrospective case-control study was conducted with 800 mothers at the Hyderabad Medical Complex (HMC) vaccination center in Peshawar between July and October, 2022. Infants aged 6-12 months were categorized based on timely or late CF introduction. Late initiation of CF defined as, introduction of CF beyond 30 weeks. Regression analysis was employed to scrutinize parental background and psychological elements in the study. Results: Results of Multivariate logistic regression revealed that house hold income, maternal education level, low Antenatal Care (ANC) visits, maternal belief about CF and maternal drug addiction were significant (p<0.05) factors that responsible for late starting of CF. Particularly late initiation of CF poorly effects Infant nutrition status. Conclusions: This study highlights the requirements for targeted population to advance CF practices in Peshawar. Such intervention promises to improve child health in the region, emphasizing the importance of proactive measures to address this concern